Incenter: five solved problems proposed for the International Mathematics Olympiad - López Linares, Juan (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2025)
Among the centers of triangles, incenter, the meeting point of the bisectors, is one of the best known due to its wide use in various fields of Mathematics and Physics. Five problems proposed for the International Mathematics Olympiad are discussed in detail. The proofs involved in the solutions are complemented by the availability of the respective links to the interactive figures using GeoGebra. It is expected that the article can be appreciated both by students preparing for the final stages of national or international competitions and by teachers interested in Olympic challenges.